Mathematics Literacy of Class Ix Students of Smp Pelita 1 Jakarta from Learning Style and English Ability (Universitas Negeri Semarang, 2022)
In this research to analyze differences in learning styles and English language ability on the mathematical literacy of grade IX students of SMP Pelita 1 West Jakarta. The methodology used in this research is sequential mixed methods type explanatory sequential. Data collection techniques used is Documents, Questionnaires, Tests, and Interviews. One Way Anova test is used to determine the difference in mathematical literacy between learning styles. Correlation analysis was used to determine the correlation between English language ability and mathematical literacy. The analysis to find out the differences in learning styles and English language skills on mathematical literacy was carried out by conducting a two-way analysis and deepened by data triangulation. Based on the results of the study, the subject of Assimilation group I had mathematical literacy which included the seven components of mathematical literacy. Students' understanding of learning styles and their English language ability will make it easier for students to understand the seven components of mathematical literacy.